CHARLOTTE ANNA PERKINS GILMANâ€™S SELECTED POEMS: A REFLECTION OF GENDER INEQUALITY (PANOPTICON: Journal of English Studies, 2022)
The study entitled â€œCharlotte Anna Perkins Gilmanâ€™s Selected Poems: A Reflection of Gender Inequalityâ€ aims to find out what aspects or things that can influence gender inequality and examine the effects of gender inequality on women characters portrayed in poems by Charlotte Anna Perkins Gilman. The object of this study is taken from the poems by Charlotte Anna Perkins Gilman. This study uses a qualitative research method, where the data is collected by reading the poems by Gilman, analyzing the issue of gender inequality contained in Gilman's poems, then describing in an analysis. Meanwhile, the data were analyzed in the form of a paragraph of exposition of the stanza which will be taken as the quotes for the case under study using the gender inequality theory by Judith Lorber (2001). The result of the study is showing that the aspects of gender inequality come from economic structure, material aspects, and family. Meanwhile, the effects result in the type of womenâ€™s work, sexuality, and emotions. Gilman's poems raise the issue or theme of women.Keywords: Poems, gender,  gender inequality.